Dystonia-like behaviors and impaired sensory–motor integration following neurotoxic lesion of the pedunculopontine tegmental nucleus in mice - Su, Jun-Hui; Hu, Yao-Wen; Song, Yun-Ping; Yang, Yi; Li, Ruo-Yu; Zhou, Kai-Ge; Hu, Ling; Wan, Xin-Hua; Teng, Fei; Jin, Ling-Jing (Frontiers in Neurology, 2023)
The pedunculopontine nucleus (PPTg) is a vital interface between the basal ganglia and cerebellum, participating in modulation of the locomotion and muscle tone. Pathological changes of the PPTg have been reported in patients and animal models of dystonia, while its effect and mechanism on the phenotyping of dystonia is still unknown. In this study, a series of behavioral tests focusing on the specific deficits of dystonia were conducted for mice with bilateral and unilateral PPTg excitotoxic lesion, including the dystonia-like movements evaluation, different types of sensory-motor integrations, explorative behaviors and gait. In addition, neural dysfunctions including apoptosis, neuroinflammation, neurodegeneration and neural activation of PPTg-related motor areas in the basal ganglia, reticular formations and cerebellum were also explored. Both bilateral and unilateral lesion of the PPTg elicited dystonia-like behaviors featured by the hyperactivity of the hindlimb flexors. Moreover, proprioceptive and auditory sensory-motor integrations were impaired in bilaterally lesioned mice, while no overt alterations were found for the tactile sensory-motor integration, explorative behaviors and gait. Similar but milder behavioral deficits were found in the unilaterally lesioned mice, with an effective compensation was observed for the auditory sensory-motor integration. Histologically, no neural loss, apoptosis, neuroinflammation and neurodegeneration were found in the substantia nigra pars compacta and caudate putamen (CPu) following PPTg lesion, while reduced neural activity was found in the dorsolateral part of the CPu and striatal indirect pathway-related structures including subthalamic nucleus, globus pallidus internus and substantia nigra pars reticular. Moreover, the neural activity was decreased for the reticular formations such as pontine reticular nucleus, parvicellular reticular nucleus and gigantocellular reticular nucleus, while deep cerebellar nuclei were spared. In conclusion, lesion of the PPTg could elicit dystonia-like behaviors through its effect on the balance of the striatal pathways and the reticular formations.